Research methods are made by questioning: The postdisciplinary challenge of networked learning - Jandri´ć, Petar (Proceedings of the International Conference on Networked Learning, 2014)
This paper describes development of networked learning using Fraser’s powerful analogy between human migration and scientific research. It recognises that most contributions to the field are developed in diverse and often mutually incommensurable research traditions from education to engineering, and identifies dialogue across different conceptual frameworks as the main challenge in their interpretation. It explores the rise of disciplinarity, and exposes its dialectical relationships with education and class. Based on wide body of research developed by members of Frankfurt School of Social Science and their successors, it analyses the relationships between technologies, society and human beings and asserts that the rise of technoscience is dialectically intertwined with the rise of disciplinarity. Moving on to the present, the paper shows that exponential rise in complexity of our tools, characteristic for the network society, has transformed disciplinarity into the new normality. During the process, it has reinforced the existing power relationships and supported further social stratification. In the network society, disciplinarity bears exactly the same consequences as in earlier historic periods. However, the stakes are much higher. Contemporary disciplinarity has significantly reduced blue-skies research to applied research, caused rapid commodification of education, and actively contributed to various environmental crises. On such basis, the paper proposes that networked learning should be analysed beyond traditional disciplinarity. It acknowledges epistemological consequences of such fundamental changes in scientific understanding of the world, and evokes a new postdisciplinary intellectual universe based on the ruins of traditional disciplinary structures. Finally, the paper briefly outlines the main postdisciplinary approaches: multidisciplinarity, interdisciplinarity, transdisciplinarity and antidisciplinarity. It warns that the outlined approaches are currently still in flux, briefly analyses their mutual relationships, and links them to issues pertaining to networked learning. On such basis, the paper proposes that postdisciplinary approaches might transcend methodological restrictions inherent to disciplinary research methodologies and provide the field of networked learning with a unified explanatory framework. Recognising that validity and verifiability of our research methods are still grounded in various disciplinary frameworks, it concludes that there is a long way from this modest proposal to its full realisation and calls for further investigation of postdisciplinary research methods for networked learning.